Endoscopic full-thickness resection versus endoscopic submucosal dissection in the treatment of colonic neoplastic lesions ≤ 30 mm-a single-center experience - Falt, Přemysl; Zapletalová, Jana; Urban, Ondřej (Surgical endoscopy, 2022)
Endoscopic full-thickness resection (FTR) is a novel technique of endoscopic treatment of colorectal neoplastic lesions not suitable for endoscopic polypectomy or mucosal resection. FTR appears to be a reasonable alternative to technically demanding endoscopic submucosal dissection (ESD) for lesions ≤ 30 mm. However, comparison between FTR and ESD has not been published yet and their mutual positioning in the treatment algorithm is still unclear. The purpose of the analysis was to evaluate efficacy and safety of FTR in the treatment of colorectal lesions ≤ 30 mm by comparing prospectively followed FTR cohort to retrospective ESD cohort in the setting of single tertiary endoscopy center. Primary outcomes were technical success rate, R0 resection and curative resection rate, and complication rate. A total of 52 patients in FTR and 50 patients in ESD group were treated between 2015 and 2018. Technical success rate was significantly higher in FTR group (92 vs. 74%, P = 0.01) as well as R0 resection rate (85 vs. 62%, P = 0.01) and curative resection rate (75 vs. 56%, P = 0.01). Complications occurred more frequently in ESD group (40 vs. 13%, P = 0.002), mainly due to high incidence of electrocoagulation syndrome (24 vs. 0%). Total procedure time was substantially shorter in FTR group (26.4 ± 11.0 min vs. estimated 90-240 min). Local residual neoplastic lesions were detected numerically more often in FTR group (12 vs. 5%, P = 0.12). No patient died during follow-up. Compared to ESD, FTR proved significantly higher technical success rate, higher R0 and curative resection rate, and shorter procedure time. In the FTR group, there were significantly less complications but higher incidence of local residual neoplasia. Further research including randomized trials is needed to compare both resection techniques.
Keywords: Neoplasm Recurrence, Local; Colorectal Neoplasms; Endoscopic submucosal dissection; Colorectal cancer; kolorektální nádory; endoskopická mukózní resekce; lidé; retrospektivní studie; Endoscopic Mucosal Resection; výsledek terapie; Endoscopy, Gastrointestinal; Retrospective Studies; Endoscopic full-thickness resection; Treatment Outcome; gastrointestinální endoskopie; lokální recidiva nádoru; Humans